Analisis Konten Buku Teks IPA Terpadu Kelas VIII Semester 1 Ditinjau Dari Aspek Literasi Saintifik - Risma, Mutia; Rahmayani, Rahmayani; Handayani, Fitria (JURNAL EKSAKTA PENDIDIKAN (JEP), 2019)
Science learning has an important role for students to understand natural phenomena with scientific methods. Science learning is taught in an integrated manner and contains literacy in it. Skills in literacy are needed to help students understand learning resources. One type of literacy is scientific literacy. Scientific literacy is the ability to understand or get involved with science issues and ideas around the environment. Scientific literacy consists of four aspects, namely 1) the scientific context, 2) the scientific process, 3) the scientific concept and 4) the scientific attitude. This research is a descriptive research that contains a description of the object under research. The object of this research is the integrated science textbook for grade VIII in junior high school. The instrument used in the form of a questionnaire assessment of integrated science textbooks related to scientific literacy aspects. The results showed that, among the five textbooks researched, the best book reviewed in terms of the scientific context and the scientific process was book D with grades of 78.6 and 78.1, respectively. In terms of scientific concepts, the best integrated science textbooks are books A and D with a value of 82.1. Meanwhile, the integrated science textbook that is good to use is seen from the aspect of scientific attitude is book E with a value of 75. After processing the data, it is found that the best book used to improve students' scientific literacy ability is book D with a value of 77.4.